The first experiments in SST-1. (19th June 2015) - Pradhan, S.; Khan, Z.; Tanna, V.L.; Sharma, A.N.; Doshi, K.J.; Prasad, U.; Masand, H.; Kumar, Aveg; Patel, K.B.; Bhandarkar, M.K.; Dhongde, J.R.; Shukla, B.K.; et al.
Abstract: A steady state superconducting tokamak (SST-1) has been commissioned after the successful experimental and engineering validations of its critical sub-systems. During the 'engineering validation phase' of SST-1; the cryostat was demonstrated to be leak-tight in all operational scenarios, 80 K thermal shields were demonstrated to be uniformly cooled without regions of 'thermal runaway and hot spots', the superconducting toroidal field magnets were demonstrated to be cooled to their nominal operational conditions and charged up to 1.5 T of the field at the major radius. The engineering validations further demonstrated the assembled SST-1 machine shell to be a graded, stress–strain optimized and distributed thermo-mechanical device, apart from the integrated vacuum vessel being validated to be UHV compatible etc. Subsequently, 'field error components' in SST-1 were measured to be acceptable towards plasma discharges. A successful breakdown in SST-1 was obtained in SST-1 in June 2013 assisted with electron cyclotron pre-ionization in the second harmonic mode, thus marking the 'first plasma' in SST-1 and the arrival of SST-1 into the league of contemporary steady state devices. Subsequent to the first plasma, successful repeatable plasma start-ups with E  ∼ 0.4 V m −1, and plasma current in excess of 70 kA for 400 ms assisted with electron cyclotron heating pre-ionization at a field of 1.5 T have so far been achieved in SST-1. Lengthening the plasma pulse duration with lower hybrid current drive, confinement and transport in SST-1 plasmas and magnetohydrodynamic activities typical to large aspect ratio SST-1 discharges are presently being investigated in SST-1. In parallel, SST-1 has uniquely demonstrated reliable cryo-stable high field operation of superconducting TF magnets in the two-phase cooling mode, operation of vapour-cooled current leads with cold gas instead of liquid helium and an order less dc joint resistance in superconducting magnet winding packs with high transport currents. In parallel, SST-1 is also continually getting up-graded with first wall integration, superconducting central solenoid installation and over-loaded MgB2 -brass based current leads etc. Phase-1 of SST-1 up-gradation is scheduled by the first half of 2015, after which long pulse plasma experiments in both circular and elongated configurations have been planned in SST-1.